Zinc oxide (ZnO) nanoparticles: Synthesis properties and their forensic applications in latent fingerprints development. (2022) - Verma, Rohit Kumar; Nagar, Varad; Aseri, Vinay; Mavry, Badal; Pandit, Pritam P.; Chopade, Rushikesh L.; Singh, Apoorva; Singh, Anubhav; Yadav, Vijay Kumar; Pandey, Kamakshi; Sankhla, Mahipal Singh
Abstract: A person's identity is determined by their fingerprints since they are distinct and one of a kind. Numerous techniques have been developed by experts to find latent fingerprints at crime scenes. With the acquiescence of nanotechnology in different fields of forensic science, the fingerprint development method has also advanced with the use of nanoparticles. In this study, one such nanoparticle has been developed and used as an application for fingerprint development. Zinc oxide (ZnO) is a chemical substance that is made up of inorganic elements. A chemical technique was used to make stable zinc oxide nanoparticles. Zinc oxide nanoparticles were created at 60 °C using a modified method that included zinc chloride and sodium hydroxide. We concentrated on the synthesis of ZnO nanoparticles, which entails the production and application of materials with a size of less than 100 nm in one or more dimensions and a cone-shaped morphology. The synthesis of pure phase ZnO nanoparticles was confirmed by SEM and XRD. The developed ZnO nanoparticles were then used in latent fingerprint detection as an application of this study. Developed fingerprints gave excellent results on all kinds of surfaces be they porous, semi-porous, or non-porous. These powders can serve as a replacement for the traditional powders currently in use by forensic scientists.